Kompetensi Guru Besar dan masalah pelaksanaan kurikulum standard sekolah rendah di sekolah kebangsaan daerah Muar - Md. Top, Zaharah (2013)
This mixed-method study aims to identify the competencies needed by the headmasters to allow them to monitor the implementation of the Primary School Standard Curriculum and the problems faced in the execution of it in primary schools in Muar District. Quantitative research through questionnaire survey conducted on 90 headmasters and qualitative research through interviews had been conducted over 3 headmasters and 3 teachers of KSSR. The findings indicated that the headmasters needed to have knowledge competency of the basic concepts of KSSR at a high level with its mean value of 4.59. The knowledge competency of KSSR management also showed a high mean value which was 4.55 and the mean value of the knowledge competency in teaching KSSR was 4.54. The interview findings showed that the problem faced by the headmasters was their lack of competency in performing observation on KSSR subjects. The findings also indicated that during observations, teachers were concerned about the misconception of their headmaster for their failure in classroom control during classroom activities. The teachers worried that they would be observed without prior notice and the explanation of the lesson could not be done. Based on the findings, the best observation process was through clinical observation. The findings also showed that teachers were having problems recording the students’ achievements online, heavy workload in preparing teaching aids and materials as evidence for the assessments. Teachers were also required to use a lot of papers for the assessments and ICT facilities to implement the World of Science and Technology modules.